The many masks of cutaneous Lyme disease. (12th October 2015) - Miraflor, Allen P.; Seidel, Gregory D.; Perry, Ann E.; Castanedo‐Tardan, Mari Paz; Guill, Marshall A.; Yan, Shaofeng
Abstract : Early cutaneous Lyme disease, erythema migrans, may show different histopathologic patterns. The intent of this case series is to raise awareness of these findings to prevent misdiagnosis and keep this entity in the differential. Erythema migrans develops after a tick bite and subsequent infection with the spirochete, Borrelia burgdorferi . It most commonly manifests as a solitary, annular lesion with a bull's‐eye appearance. Classic histopathologic findings include superficial and deep perivascular and interstitial lymphocytic infiltrates mixed with plasma cells and eosinophils. We identified and reviewed eight cases of early erythema migrans. Each patient had confirmed B. burgdorferi IgM seropositivity and IgG seronegativity. Histopathologic evaluation of these biopsies reveals a diversity of patterns. Seven of eight cases show sparse to mild perivascular and interstitial mixed infiltrate of variable amount of lymphocytes, eosinophils, neutrophils and plasma cells, with only one case showing a dense inflammatory infiltrate. Epidermal changes such as spongiosis and interface change are seen in some cases. Additionally, perineural lymphocytic infiltrate is seen in one case, periadnexal infiltrate in four cases and pigment incontinence in one case. Based on variable histopathologic findings, it is important to consider erythema migrans in the differential diagnosis for prompt diagnosis and treatment.